Metabolic RNA Labeling and Translating Ribosome Affinity Purification for Measurement of Nascent RNA Translation - Hirotatsu Imai; Akio Yamashita (Bio-Protocol)
Regulation of gene expression in response to various biological processes, including extracellular stimulation and environmental adaptation, requires nascent mRNA synthesis and translation. Simultaneous analysis of the coordinated regulation of dynamic mRNA synthesis and translation using the same experiment remains a major challenge in the field. Here, we describe a step-by-step protocol for the simultaneous measurement of transcription of nascent mRNA and its translation at the gene level during the acute unfolded protein response (UPR) in HEK293 cells by combining 4-thiouridine metabolic mRNA labeling with translational ribosome affinity purification (TRAP) using a monoclonal antibody against evolutionarily conserved ribosomal P-stalk proteins (P-TRAP). Since P-TRAP captures full-length RNAs bound to ribosomes, it is compatible with 3' mRNA-seq, which analyzes the uridine-rich 3' UTRs of polyadenylated RNAs, allowing robust quantification of T>C conversions. Our nascent P-TRAP (nP-TRAP) method, in which P-TRAP is combined with metabolic mRNA labeling, can serve as a simple and powerful tool to analyze the coordinated regulation of transcription and translation of individual genes in cultured cells.